Religious Moderation from Below: Defining Religious Moderation from the Perspectives of Catholic Religious Teachers - Asmara, Alexander Hendra Dwi (MAHABBAH: Journal of Religion and Education, 2024)
Religious moderation has been envisioned by the Indonesian government since 2019. However, religious moderation has not been implemented successfully, especially in the field of Catholic Religious Education. The purpose of this research is to find out how Catholic religious teachers perceive religious moderation in their teachings. This research paper employs a qualitative design. Data is collected using deep interviews with five Catholic religious teachers from Yogyakarta, Solo, Semarang, and Jakarta. The findings show that most of the informants are aware of the religious moderation proposed by the government. Nevertheless, the informants shared that they were less motivated to implement religious moderation in their Catholic religious education subject because of several reasons, such as, the lack of support from school policy makers, the absence of government trainings or modules related to religious moderation, and the density of the curriculum in schools makes it difficult for teachers to add other material, including religious moderation